Impact of Unexpected Death in Simulation: Skill Retention, Stress and Emotions - Boet, Sylvain; Schebesta, Karl; Khanduja, Kristina; Andrews, Meghan; LeBlanc, Vicki; Bould, M. Dylan (Université d'Ottawa | University of Ottawa, 2018)
Background High-fidelity simulation is an increasingly used teaching tool that is proven to be effective for learning. According to the literature, by gradually increasing stress and emotions, more effective learning can be achieved. However, allowing the simulated patient to “die”, as a deliberate stressor, is controversial. There is no previous research on the educational effect of letting a simulated patient die. We aim to evaluate the effects of simulated unexpected death on skill retention, stress levels, and emotions. We hypothesize that the occurrence of unexpected death will impact skill retention, and will be associated with higher stress levels and stronger emotions. Methods After Institutional Research Ethics Board approval, 56 residents and fellows of different medical specialties will be randomized to either the intervention (unexpected death) or control (survive) group. Participants from both groups will have to individually manage a simulated cardiac arrest crisis. In the intervention group, the scenario will end by the death of the simulated patient, whilst in the control group the simulated patient will survive. Each participant will be immediately debriefed by a trained instructor. Three months later, skill retention will be assessed in a similar scenario. Crisis management performance of all scenarios will be rated by 2 blinded raters. Biological stress, cognitive appraisal, and emotions will be measured during both scenarios. Implications The impact of simulated unexpected death on skill retention of residents and fellows will provide instructors with evidence to optimize scenario design and approach the role of stress and emotions in simulation-based education.
Keywords: Simulation; Crisis Resource Management (CRM) Skills; Stress; Advanced Cardiovascular Life Support (ACLS) Skills